Differentiated Assessment Practices in a Montessori-Based Elementary School: A Qualitative Study on Implementation, Challenges, and Benefit - Agung Ayu Dyah Permata Sari; Ni Nyoman Padmadewi; I G A Lokita Purnamika Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Differentiated assessment has become an important approach to addressing students’ diverse learning needs; however, evidence regarding its implementation in Montessori primary education remains limited. This study aimed to investigate the implementation of differentiated assessment, identify the challenges faced by teachers, and examine its benefits. A qualitative case study design was employed involving two teachers responsible for fourth-, fifth-, and sixth-grade students. Data were collected through surveys, classroom observations, and semi-structured interviews using an open-ended questionnaire, an observation sheet, and an interview guide. The questionnaire was administered over one week, followed by one week of classroom observations and subsequent interviews. The collected data were analyzed using thematic analysis. The findings revealed that differentiated assessment was implemented through well-planned learning activities, formative assessment practices, varied assessment tasks and products, and a prepared learning environment. Teachers’ experience and professional competence were identified as key factors supporting effective implementation, while limited professional training remained a major challenge. The implementation of differentiated assessment also contributed positively to students’ academic performance and supported teachers’ professional development. In conclusion, differentiated assessment is an effective approach for accommodating diverse learning needs in Montessori classrooms, although its success depends on teachers’ competencies and institutional support. These findings highlight the importance of continuous professional development to strengthen teachers’ capacity in implementing differentiated assessment effectively.